γ-Stearolactone ring-opening by zeolites for the production of branched saturated fatty acids - Bos, Jelle W; Vloedgraven, Job G A; Wiedemann, Sophie C C; van Dongen, Leo; Moonen, Roel C J; Wels, Bas; Berben, Peter H; Reesink, Bennie H; de Peinder, Peter; Vogt, Eelco T C; Weckhuysen, Bert M (Catalysis science & technology, 2024)
C branched saturated fatty acids (BSFA) are used as ingredients in cosmetics and lubricants and are produced the hydrogenation of C branched unsaturated fatty acids (BUFA). Industrial-grade C BUFA contain the odorous by-product γ-stearolactone (GSL), which must be removed by acid-catalysed ring-opening of GSL into oleic acid. Zeolites such as Y and beta can facilitate the ring-opening, but due to the dimensions of GSL the activity is expected to be limited by diffusion into the micropores. Hence, zeolites Y and beta were modified hydrothermal treatment and acid leaching and used in the GSL ring-opening reaction. While modification of zeolite beta led to a reduction in acidity of more than 50%, the material displayed much-enhanced activity compared to the parent material. In a batch reactor steamed beta zeolites were able to convert all GSL within 2 h, compared to 5 h for the parent zeolite. Infrared spectroscopy studies of adsorbed pyridine reveal that likely a beneficial change in Brønsted/Lewis acid site ratio is responsible for the increased activity. Lewis acid sites in zeolites are known to catalyse double bond isomerisation, which could greatly enhance GSL conversion by reducing the reverse formation of GSL from oleic acid. We believe that these insights can be used to further improve GSL ring-opening activity and inspire research on the ring-opening of other biomass derived lactones.